Do We Need More Women in Power? Gender, Public Policy, and Development in Bolivia - Patricia Ya\~nez-Pagans (Inter-American Development Bank (IDB), 2014)
This paper evaluates the impacts of increasing female representation in Bolivian municipal councils on public policy choices and welfare outcomes. By combining detailed administrative panel data on municipal expenditures and revenues together with electoral data, an innovative regression discontinuity design (RDD) is applied. As opposed to previous studies, the RDD approach proposed is unique since it is implemented to systems of proportional representation. Findings indicate that municipalities with women councilors devote more resources to social investments. In particular, women politicians prioritize education, health, and environmental protection expenditures giving less attention to infrastructure investments. The impacts of higher female representation appear only some years after the elections, highlighting the importance of training and experience. Despite changes in public policy choices there is weak evidence on the links with final welfare outcomes.
hdl:11319/6741
Keywords: O12; J16; P16; 330; Gender; Politics; Public Policy; Development